Evaluasi Pembelajaran dalam Pelatihan Integrasi AI untuk Asesmen Pembelajaran Bagi Guru MTs - Hirnanda Dimas Pradana; Alim Sumarno (Jurnal Penelitian Pendidikan IPA, 2025)
This study evaluates learning in training activities on applying Artificial Intelligence (AI) in formative assessment for Madrasah Tsanawiyah (MTs) teachers, especially at MTs NU Trate Gresik. The training evaluation used the CIPP (Context, Input, Process, Product) model approach to identify the learning effectiveness at each training stage. The findings show that in the context aspect, there is a significant gap between conventional evaluation practices and the need for technology-based assessments. The input aspect shows that the training has been designed contextually with expert support and technology such as Quizizz AI Generator and adaptive Google Forms. The interactive training process involved high participation despite facing technical obstacles that were successfully overcome through intensive mentoring. The product aspect shows a fundamental transformation in learning evaluation in the classroom, marked by increased teachers’ abilities in designing and implementing AI-based assessments. The results of the paired sample t-test showed a significant increase in teacher evaluation competency, from an average score of 60.98 to 83.98 in the post-test (p=0.000). This finding indicates that the training improves conceptual knowledge and facilitates changes in assessment practices towards a more diagnostic, adaptive, and reflective approach. Thus, this training strengthens teacher capacity in supporting the digital transformation of education in the madrasah.